Mechanochemical bottom-up synthesis of phosphorus-linked, heptazine-based carbon nitrides using sodium phosphide - Fiss, Blaine G.; Douglas, Georgia; Ferguson, Michael; Becerra, Jorge; Valdez, Jesus; Do, Trong-On; Friščić, Tomislav; Moores, Audrey (Beilstein Journal of Organic Chemistry, 2022)
Herein, we present the bottom-up, mechanochemical synthesis of phosphorus-bridged heptazine-based carbon nitrides (g-h-PCN). The structure of these materials was determined through a combination of powder X-ray diffraction (PXRD), X-ray photoelectron spectroscopy (XPS), 31P magic angle spinning nuclear magnetic resonance (MAS NMR), density functional theory (DFT) and electron energy loss spectroscopy (EELS). Compared to traditional furnace-based techniques, the presented method utilizes milder conditions, as well as shorter reaction times. Both samples of g-h-PCN directly after milling and aging and after an hour of annealing at 300 °C (g-h-PCN300) show a reduction in photoluminescent recombination, as well as a nearly two-time increase in photocurrent under broad spectrum irradiation, which are appealing properties for photocatalysis.
Keywords: carbon nitride; density functional theory; mechanochemistry; phosphorus; photochemistry